Reinforced concrete sandwich panels with autoclaved aerated concrete infill / Abdel-Mooty M ... [et al.] - M., Abdel-Mooty; M.A., Al Kashif; E., Fahmy; M., Abou Zeid; M., Haroun (2012)
Reinforced concrete sandwich panels are composed of two thin concrete outer layers separated by a lightweight, insulating, and usually weaker inner layer. They provide improved thermal insulation characteristics and are easier to construct due to their reduced weight. The composite action of the panel is achieved mainly through the use of shear connectors between the two outer layers due to the very low shear resistance of the inner insulating layer. However, the shear connectors reduce the thermal insulation property of the panel through bridging the two outer layers with heat conducting media. In this research, the use of lightweight Autoclaved Aerated Concrete (AAC) blocks is suggested to provide shear coupling and maintain the bending capacity of the panel. An experimental program is developed to study the load capacity and deformation of this system through testing full scale RC sandwich panels with AAC blocks infill in 4-point bending test until its failure. Different design parameters are examined in this test program including: the surface roughness of the AAC layer, and the use of steel shear connectors. The results show the efficiency of AAC infill in resisting shear and maintaining the bending capacity.